SYNTACTICAL ERRORS MADE BY THE STUDENTS IN WRITING THESIS - Faidah Yusuf; Jumriana Jumriana (Elite : English and Literature Journal, 2015)
Abstract The Analysis of Syntactical Errors Made by the Students in Writing Thesis aimed to find out the types of syntactical errors made by the students in writing thesis and to find out the most frequent type of errors made by the students in writing thesis. The writer used Politzer and Romirez’s theory focusing on the Syntactical errors. This study found the errors made by students were in the term of noun phrase, verb, verb construction, and transformation. Then, the most frequent error found was in the noun phrase term with 48.7%. The researcher suggests the English teachers to give reinforcement for the students about the basic rules of constructing sentences.Abstrak Analisa Kesalahan Sintaksis oleh Mahasiswa dalam Penulisan Skripsi. Penelitian ini bertujuan untuk memperoleh jenis kesalahan sintaksis yang dilakukan oleh siswa dalam menulis skripsi dan kesalahan sintaksis yang paling sering dilakukan. Penulis menggunakan teori Politzer dan Romirez mengenai kesalahan sintaksis. Hasil penelitian memperlihatkan bahwa kesalahan yang dilakukan mahasiswa adalah pada noun phrase, verb, verb construction, and transformation. Jenis kesalahan yang paling sering dilakukan adalah pada noun phrase (47.8%). Penulis menyarankan dosen bahasa Inggris untuk memberikan penguatan pada mahasiswa mengenai aturan dasar mengenai constructing sentences.